Analyze the Portrayal of Indian Society's Transformation in the Post-Independence Era Through Literature (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This study explores the portrayal of Indian society's transformation in the post-independence era through the lens of literature. Indian authors, across various regions and time periods, have used literature as a powerful medium to reflect, critique, and document the socio-economic, political, and cultural changes shaping the nation. The paper examines key themes such as social and economic inequalities, urbanization and modernization, political and cultural identity, and the impact of globalization. Drawing on works by notable authors like R.K. Narayan, Salman Rushdie, Arundhati Roy, Mahasweta Devi, and Aravind Adiga, this research highlights how literature captures the struggles and aspirations of a nation redefining itself after colonial rule. From the caste and class hierarchies depicted in Mulk Raj Anand's Untouchable to the exploration of globalization's effects in Aravind Adiga's The White Tiger, the analysis underscores literature’s role in amplifying marginalized voices and challenging dominant narratives. By integrating regional perspectives and temporal shifts, the study reveals the evolving themes and stylistic innovations in Indian literature. It concludes that literature not only mirrors the transformation of Indian society but also serves as a critical tool for understanding its complexities, offering invaluable insights into the nation's collective identity and cultural resilience. This paper contributes to the discourse on post-independence Indian literature as a dynamic reflection of societal change and continuity.